Etika Komunikasi Driver Gojek Online Dalam Pelayanan Publik di Lingkungan Kampus A Universitas Islam Negeri Raden Fatah Palembang - Lestari, Cornelia Endang; Murdiati, Eni; Duku, Sumaina (Indonesian Journal Publisher, 2024)
This research aims to find out the communication ethics of online Gojek drivers in public services within campus A of Raden Fatah State Islamic University, Palembang. Using interpersonal communication theory and qualitative research methods. Ethics is understood as a set of values, morals, principles or standards of behavior shared by a person, group or society and even a nation. So Ethics is a science that discusses what is good and what is bad and about moral rights and obligations (morals). When communicating with customers or consumers, there are several ways that need to be considered, communicating is not just conveying information. However, also sensitivity to consumer feelings through the art of correct communication, namely by giving a good impression to customers because the first impression is the first thing the customer notices. Meanwhile, public services are one part of achieving the government's targets which aim to create an independent and prosperous society. The results of this research show that the communication ethics of online Gojek drivers within campus A of Raden Fatah State Islamic University, Palembang, requires several things to be done by an online Gojek driver, namely using a real identity, providing the best service, increasing the trust of all parties by establishing good direct communication. or indirectly, Do not select incoming orders, Express polite objections to customers if the customer wants to stop or stop by other than their destination. Meanwhile, the communication ethics of online Gojek drivers, especially those on campus A, Raden Fatah State Islamic University, Palembang, is to provide good and polite etiquette and provide satisfaction to customers in accordance with the customer's wishes or desires. Success in excellent service cannot be separated from the ability to choose the concept of personal approach or interpersonal communication.